The place of truth in human existence (Iter, 2022)
Tha author claims that truth is a matter o f rather little concern withinhuman existence. The search o f truth is actually the scope o f scientific andlogical thought; but art and poetry, as well as human action, individualor collective, do not aim at truth and have other ends. As for i(religioustruths ”, they are, strictly speaking, beliefs, not truths, since, in spite o ftheir meaning for human beings, they do not share the features o f truth,being unprovable and not subject to the principies o f contradiction or o fsufficient reason.
Keywords: Truth, reason, action, imagination